METHODOLOGICAL ASPECTS FOR PROJECTIONS OF GREENHOUSE GAS EMISSIONS IN THE AGRICULTURAL SECTOR - Bertosh, Evgeniya (Journal of the Belarusian State University. Ecology, 2026)
Projections of Greenhouse Gas Emissions is a key analytical tool for development of National Climate Strategies, updating Nationally Determined Contributions (NDCs), assessing the effectiveness of climate mitigation measures, and planning socio-economic development. This paper presents the methodological approaches for projections of greenhouse gas emissions in the agricultural sector of the Republic of Belarus up to 2035, developed in the context of predation of the third Nationally Determined Contribution under the Paris Agreement. Based on international guidelines and national data, three development scenarios were developed. Key scenario assumptions were substantiated, reflecting current trends in livestock production, crop cultivation, and fertilizer application. A list of priority low emission measures was identified, including biogas technologies, precision and organic farming, conservation of degraded peatlands, and optimization of cattle feeding practices. For each measure, specific efficiency indicators (emission reductions per unit of implementation) were calculated, enabling a quantitative assessment of their contribution to reducing greenhouse gas emissions. The methodology and results of this study can be used in mapping of climate policy in Belarus.
Keywords: greenhouse gases; agriculture; scenario modeling; emission projections; nationally determined contribution; climate policy; low-carbon technologies